O33: PROSPECTIVE RISK ASSESSMENT ALONE DOES NOT IMPROVE 30-DAY MORTALITY IN EMERGENCY LAPAROTOMY PATIENTS. (27th April 2021) - Vavilov, S; Pockney, P
Abstract: Introduction: Emergency laparotomy still carries a high mortality risk. According to the latest National Emergency Laparotomy Audit (NELA) report, half of the patients without pre-operative risk scoring had a higher observed than predicted mortality. Data from Perth, Australia also suggests that pre-operative scoring improves mortality. The aim of this study was to determine if a prospective risk assessment has an independent favourable effect on outcomes. Method: A retrospective review of all emergency abdominal surgeries meeting NELA inclusion criteria undertaken at four different-sized Australian surgical centres was performed between April 2015 and December 2018. A predicted and observed mortality was assessed in prospectively and retrospectively risk-stratified patients. Result: There were 852 patients charts reviewed during the study period. Patient demographics included 404 males (47.4%), mean age: 69 years, median American Society of Anaesthesiologists score: 3, mean length of stay: 14.0 days and mean ICU length of stay: 1.8 days. There were 72 patients who died within 30 days (8.5%). Median preoperative P-POSSUM score was 6.9%, median preoperative NELA score – 5.2%. A total of 27/133 (20.3%) patients who were scored  prospectively  died within 30 days; 45/719 (6.3%)  retrospectively  scored patients died within 30 days. Neither of these rates was very different from the predicted. Conclusion: 30-day mortality in emergency laparotomy patients in Hunter New England region, Australia, compares favourably with the latest mortality figures reported by NELA. However, contrary to other publications, prospective scoring alone did not have any beneficial effect on 30-day mortality in our cohort Take-home message: Patients undergoing emergency abdominal surgery require preoperative risk assessment to improve outcomes. However, just the fact of assigning a risk score preoperatively alone does not help to improve mortality.